MEDICAMENTOS INDICADOS PARA O TRATAMENTO SINTOMÁTICO DA GRIPE: VERIFICAÇÃO DO CUMPRIMENTO DA RDC N.º 77/03 - Scheuer, Cristine; Oliveira, Karla R. d.; Lorencetti, Leonardo (Salão do Conhecimento, 2013)
Resumo